2010
DOI: 10.1007/s00209-010-0756-8
|View full text |Cite
|
Sign up to set email alerts
|

An uncertainty principle, Wegner estimates and localization near fluctuation boundaries

Abstract: We prove a simple uncertainty principle and show that it can be applied to prove Wegner estimates near fluctuation boundaries. This gives new classes of models for which localization at low energies can be proven. IntroductionStarting point of the present paper was the lamentable fact that for certain random models with possibly quite small and irregular support there was a proof of localization via fractional moment techniques (at least for d ≤ 3) but no proof of Wegner estimates necessary for multiscale anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…The term in square brackets is a structural constant that, typically, does not depend on Λ. As we showed in [3], we can find an uncertainty estimate of the form ( ) with κ independent of Λ for very general Anderson type random models. The remaining terms give the right volume dependence as well as the continuity of the single site random variables.…”
Section: Wegner Estimatessupporting
confidence: 58%
See 4 more Smart Citations
“…The term in square brackets is a structural constant that, typically, does not depend on Λ. As we showed in [3], we can find an uncertainty estimate of the form ( ) with κ independent of Λ for very general Anderson type random models. The remaining terms give the right volume dependence as well as the continuity of the single site random variables.…”
Section: Wegner Estimatessupporting
confidence: 58%
“…In [3] we showed that we have an uncertainty principle ( ) with κ independent of Λ. Moreover, for the models considered there, the other constants are uniformly bounded.…”
Section: Remarks 42mentioning
confidence: 84%
See 3 more Smart Citations